B cell subsets are activated and produce cytokines during early phases of Francisella tularensis LVS infection - Plzakova, Lenka; Kubelkova, Klara; Krocova, Zuzana; Zarybnicka, Lenka; Sinkorova, Zuzana; Macela, Ales (Microbial pathogenesis, 2014)
Francisella tularensis, a facultative intracellular Gram-negative bacterium, causes the illness tularemia. The infection of mice with live vaccine strain is considered to be a model of human tularemia. F. tularensis infects predominantly such phagocytic cells as macrophages or neutrophils, but it also infects non-phagocytic hepatocytes, epithelial cells, and murine and human B cell lines. Based on work with the murine tularemia model, we report here that F. tularensis LVS infects peritoneal CD19(+) cells - exclusively B-1a cells - early after intraperitoneal infection in vivo. The peritoneal and consequently spleen CD19(+) cells are activated by the F. tularensis LVS infection to express the activation markers from MHC class II, CD25, CD54, CD69, and the co-stimulatory molecules CD80 and CD86. As early as 12 h post-infection, the peritoneal CD19(+) cells produce IFN-γ, IL-1β, IL-4, IL-6, IL-12, IL-17, IL-23, and TNF-α. The spleen CD19(+) cells respond to infection with some delay. Moreover, the F. tularensis infected A20 B cell line activates CD3(+) spleen cells isolated from naïve mice. Thus, the data presented here suggest that B cells have all the attributes to actively participate in the induction and regulation of the adaptive immune response during early stages of F. tularensis infection.
Keywords: modely nemocí na zvířatech; slezina; peritoneum; tularemie; Antigens, CD; Activating markers; CD antigeny; cytokiny; Lymphocyte Activation; myši inbrední BALB C; podskupiny B-lymfocytů; MHC antigeny II. třídy; aktivace lymfocytů; Mice, Inbred BALB C; Spleen; F. tularensis; Time Factors; Animals; ženské pohlaví; zvířata; Tularemia; B cells; časové faktory; Disease Models, Animal; B-Lymphocyte Subsets; Cytokines; Female; Antigen-presenting function; Peritoneum; Histocompatibility Antigens Class II